Promoting and valuing neglected and underutilized species for sustainable livelihoods and climate change adaptation: insights from Kenya, Uganda, Zambia and Zimbabwe - Vernooy, Ronnie; Fusire, Marcelline; Graybill, Munkombwe; Kimani, Dominic; Mitei, Dalmus; Otieno, Gloria Atieno; Recha, Tobias (2022)
Farmers in Africa are facing unprecedented challenges to deal with changing and anomalous climates and related crop management problems caused by (new) biotic and abiotic stresses. Current seed systems are not serving their needs due to various shortcomings and constraints. Although there have been some scattered successful efforts to provide solutions to resolve seed systems bottlenecks, there is an urgent need to bring these solutions to scale. The Resilient seed systems initiative, coordinated by the Alliance of Bioversity International and CIAT, is a long-term effort that envisions that African smallholder farmers will have a secure and diversified supply of quality seeds (and other planting materials) suitable for local conditions that contribute to more sustainable livelihoods and stronger capacity to adapt to climate change. They will receive useful and timely information about seeds and climate services, will be better able to access seed in time of environmental and societal stress, will benefit from technical and financial support from formal sector agencies, and will be recognized and supported as actors in the seed system. Central to the initiative is the engagement with multiple stakeholders including the private seed sector, civil society organizations (local seed businesses, Farmer Field Schools, community seed banks) and local (county government) and national governmental and non-governmental organizations, that are well-positioned to take up and further develop strategies, methods and tools and integrate them in their daily work. While focusing on Kenya, Uganda, Zambia, and Zimbabwe, the initiative strategically integrates a (sub)regional dimension, particularly for the purposes of knowledge exchange, capacity building and policy analysis and advocacy.